Acute Kidney Injury and Risk of Death After Elective Surgery: Prospective Analysis of Data From an International Cohort Study. (May 2019) - Chaudery, Hannan; MacDonald, Neil; Ahmad, Tahania; Chandra, Susilo; Tantri, Aida; Sivasakthi, Velayuthapillai; Mansor, Marzida; Matos, Ricardo; Pearse, Rupert M.; Prowle, John R.
Abstract : BACKGROUND: Postoperative acute kidney injury (AKI) is associated with a high mortality rate. However, the relationship among AKI, its associations, and mortality is not well understood. METHODS: Planned analysis of data was collected during an international 7-day cohort study of adults undergoing elective in-patient surgery. AKI was defined using Kidney Disease Improving Global Outcomes criteria. Patients missing preoperative creatinine data were excluded. We used multivariable logistic regression to examine the relationships among preoperative creatinine-based estimated glomerular filtration rate (eGFR), postoperative AKI, and hospital mortality, accounting for the effects of age, major comorbid diseases, and nature and severity of surgical intervention on outcomes. We similarly modeled preoperative associations of AKI. Data are presented as n (%) or odds ratios (ORs) with 95% confidence intervals. RESULTS: A total of 36, 357 patients were included, 743 (2.0%) of whom developed AKI with 73 (9.8%) deaths in hospital. AKI affected 73 of 196 (37.2%) of all patients who died. Mortality was strongly associated with the severity of AKI (stage 1: OR, 2.57 [1.3–5.0]; stage 2: OR, 8.6 [5.0–15.1]; stage 3: OR, 30.1 [18.5–49.0]). Low preoperative eGFR was strongly associated with AKI. However, in our model, lower eGFR was not associated with increasing mortality in patients who did not develop AKI. Conversely, in older patients, high preoperative eGFR (>90 mL·minute −1 ·1.73 m −2 ) was associated with an increasing risk of death, potentially reflecting poor muscle mass. CONCLUSIONS: The occurrence and severity of AKI are strongly associated with risk of death after surgery. However, the relationship between preoperative renal function as assessed by serum creatinine-based eGFR and risk of death dependent on patient age and whether AKI develops postoperatively.